A Review of a Preliminary Quantitative Study and Genetic Analysis for Rare Earth Elements of Ionic Adsorption State in Phosphate Ore Deposit in Zhijin, Guizhou Province - DUAN Kai-bo; WANG Deng-hong; XIONG Xian-xiao; LIAN Wei; GAO Peng; WANG Ying-lin; ZHANG Yang (Yankuang ceshi, 2014)
Recent studies on rare earth elements (REEs) for the Phosphate Deposit in Zhijin, Guizhou show that the occurrence state of REEs is dominated by isomorphism on the basis of the positive correlation between ∑REEs content and phosphorus content. However, the understanding for the independent REE minerals state and the ionic adsorption REE state is still not clear at present. Methods of Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) analysis for REEs, quinoline phosphomolybdate gravimetry analysis for phosphorus, rock-mineral identification and laboratory beneficiation test have been carried out for the study of REE occurrence state in the deposit. The results from rock-mineral identification show the REE-phosphate ore are composed of collophane dominantly and a small quantity of clay minerals, but no independent REEs minerals have been observed. Element content analytical results indicate a positive correlation between ΣREEs and phosphorus, and even between each single REE and phosphorus, which confirm REEs occur in collophane as isomorphism state dominantly. The REEs distribution was studied by allocation and content correlation of REEs and phosphorus in the concentration, tailings and processing solution (tailing water). As a result, phosphorus only collects in the concentrate and tailings without any loss, while 11.98% of ΣREEs dissociates from ore under the reaction of strong sulfate electrolyte and enters the processing solution. It indicated that this part of REEs was adsorbed on the surface of minerals instead of in mineral crystal lattice. 11.98% of REEs are ionic adsorption REEs. The complete weathering on the condition of eternity and moisture and adsorption carriers played by collophane and clay minerals contributed to the genesis of the ionic adsorption state REEs. In summary, the occurrence state of REEs hosted in the deposit is dominated by isomorphism and partly is in an ionic adsorption state and not an independent REE mineral. Therefore, ionic adsorption is the second primary occurrence state after the isomorphism state.